Global trends in research and commercialization of exogenous and endogenous RNAi technologies for crops. (2nd January 2019) - Mat Jalaluddin, Nurzatil Sharleeza; Othman, Rofina Yasmin; Harikrishna, Jennifer Ann
Abstract: It has only been about 20 years since the first Nobel Prize-winning work on RNA interference (RNAi) in Caenorhabditis elegans was published in the journal Nature . Fast forward to today, and the use of RNA molecules as gene-silencing elements in crops has helped scientists to unveil possible solutions to the global problems of agricultural losses due to pests, viruses, pathogens, and to other abiotic and biotic stresses. The recent proliferation of publications suggests that the technology has gained significant attention and received ample funding support. In this article, an attempt has been made to visualize recent trends in Research & Development (R&D) investment in this field by analyzing top cited scholarly articles, patent trends, and commercialization activity. The publication and citation analysis identified that the development of RNAi-based crops conferring resistance against viruses, fungi, and pests are at the forefront of RNAi research and that Chinese and US institutions are the leaders in this field. The patent landscape analysis for RNAi technology over all aspects related to RNAi-derived crops provides an overview of patenting activity from a geographical, organizational, and legal perspective. Such an exercise is pivotal to industry players and public institutions aiming at creating intellectual property that is commercially appealing. An upswing in commercial interests in this technology in recent years is reflected by a consistent number of patent filings in US, European, and Chinese patent offices, with multinational giant firms as the most prolific patent filers. The expanding RNAi commercialization landscape is supported by a series of strategic partnerships, licensing agreements, and acquisitions created between agribusinesses, public research institutions, and startup companies. From key observations, we would like to highlight that such investments have very positive impacts on the development of RNAi technology. Nonetheless, the success of this technology is dependent on several factors, such as financial requirements, the complexity, and timeframe of the entire development process, as well as stringent regulations imposed by the relevant authorities. In most countries, RNAi-based transgenic crops are still considered as a genetically modified (GM) product, which necessitates the crops to undergo rigorous evaluation before approval is granted. Recent advancements in exogenous RNAi-derived biopesticides have provided a nontransgenic alternative to GM crops. However, challenges still remain in the form of technical hurdles and regulatory ambiguities surrounding this emerging technology. Its full potential remains to be realized.